2016
DOI: 10.1007/s10584-016-1657-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessing debris flow activity in a changing climate

Abstract: Future trends in debris flow activity are constructed based on bias-corrected climate change projections using two meteorological proxies: daily precipitation and Convective Available Potential Energy (CAPE) combined with specific humidity for two Alpine areas. Along with a comparison between proxies, future number of days with debris flows are analyzed with respect to different regional and global climate models, Representative Concentration Pathways (RCPs), and area for quantile mapping. Two different base p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 38 publications
0
36
0
Order By: Relevance
“…Global warming as a result of climate change is a quantifiable phenomenon (Shi et al, 2010;Gariano, et al, 2016;Turkington, et al, 2016), with a demonstrable increase in global temperatures by ~0.57°C over the last century (Fig. 1).…”
Section: Global Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…Global warming as a result of climate change is a quantifiable phenomenon (Shi et al, 2010;Gariano, et al, 2016;Turkington, et al, 2016), with a demonstrable increase in global temperatures by ~0.57°C over the last century (Fig. 1).…”
Section: Global Temperaturementioning
confidence: 99%
“…Global warming resulting from climate change has altered the occurrence frequency and intensity of many natural geohazards, including landslides, debris flows and earthquakes (Calbó et al, 2010;Coe and Godt., 2012;Seneviratne et al, 2012;Gariano and Guzzetti., 2016;Heuvel, et al, 2016;Turkington, et al, 2016;Yongming Lin, et al, 2017). As an example of the mechanism for this, research has shown that 5%-10% of global permafrost will melt if global temperatures 25 rise by 2°C, causing a significant increase in landslides and mudslides (Dong and Jia., 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, the distribution of both precipitation stations and meteorological radars is quite sparse and uneven in most mountainous regions (Wang, Chen, & Yang, 2019). This is due to their coarse resolution, insufficient number of observations, poor downscaling methods, and delayed availability (Sun et al, 2018;Turkington et al, 2016). This is due to their coarse resolution, insufficient number of observations, poor downscaling methods, and delayed availability (Sun et al, 2018;Turkington et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, most gridded precipitation data sets from climate model outputs, gauge-based precipitation, and reanalysis products, are not ideally suited for research and applications related to rainfalltriggered geological hazards. This is due to their coarse resolution, insufficient number of observations, poor downscaling methods, and delayed availability (Sun et al, 2018;Turkington et al, 2016). However, satellitebased precipitation has become a widely used approach to provide cost-effective precipitation estimates (Xu et al, 2019), which is free from most of those limitations (Prakash et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of these applications rely exclusively on the well-established concept of intensity-duration thresholds (e.g. Aleotti 2004, Guzzetti et al, 2007 and references therein), or apply other probabilistic assessments of rainfall characteristics (Berti et al, 2012;Braun and Kaitna, 2016;Turkington et al, 2016;van den Heuvel et al, 2016). Either approaches work under the implicit conjecture that rainfall is the only hydrological factor 30 controlling debris flow initiation.…”
mentioning
confidence: 99%